1996
DOI: 10.1046/j.1365-2265.1996.729549.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadotrophic hypogonadism and primary amenorrhoea associated with increased melatonin secretion from a cystic pineal lesion

Abstract: A 17-year-old girl presented with primary amenorrhoea and failure to develop secondary sexual characteristics, although her height was above the 90th centile. Endocrine investigations revealed hypogonadotrophic hypogonadism (basal LH and FSH levels < 0.5 U/l; FSH rose to 2.0 U/l and LH to 1.0 U/l after GnRH). ACTH, GH, TSH and PRL secretion were normal. A magnetic resonance scan revealed no abnormality in the pituitary, pituitary stalk or hypothalamus but demonstrated a partly cystic enhancing lesion in the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…In the KS group, serum E 2 , FSH and LH levels were elevated prior to testosterone administration and remained so during treatment. Increased melatonin levels as observed in our IGD patients were also demonstrated in other studies (Puig-Domingo et al, 1992;Ozata et al, 1996;Walker et al, 1996). The effect of sex steroids on melatonin secretion was evaluated in several studies, both in male and female patients, but revealed conflicting results (Arendt et al, 1985;Puig-Domingo et al, 1992;Delfs et al, 1994;Bartsch et al, 1995;Commentz & Willing, 1995).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the KS group, serum E 2 , FSH and LH levels were elevated prior to testosterone administration and remained so during treatment. Increased melatonin levels as observed in our IGD patients were also demonstrated in other studies (Puig-Domingo et al, 1992;Ozata et al, 1996;Walker et al, 1996). The effect of sex steroids on melatonin secretion was evaluated in several studies, both in male and female patients, but revealed conflicting results (Arendt et al, 1985;Puig-Domingo et al, 1992;Delfs et al, 1994;Bartsch et al, 1995;Commentz & Willing, 1995).…”
Section: Discussionsupporting
confidence: 74%
“…Functional melatonin receptors were demonstrated in human granulosa cell membranes (Yie et al, 1995), prostate (Gilad et al, 1996), hypothalamic suprachiasmatic nuclei and pituitary pars tuberalis (Weaver et al, 1993), suggesting that melatonin may act on the reproductive system at three sites. Abnormal melatonin secretion was demonstrated in women with hypothalamic amenorrhoea (Berga et al, 1988;Brzezinski et al, 1988), anorexia nervosa (Tortosa et al, 1989), secondary amenorrhoea (Okatani & Sagara, 1994), in patients with precocious puberty (Waldhauser et al, 1991), and in hypogonadotrophic hypogonadism (Puig-Domingo et al, 1992;Ozata et al, 1996, Walker et al, 1996.…”
mentioning
confidence: 99%
“…The lack of sustained effects of b-adrenoceptor agonists on melatonin production could be due to the low doses of b-adrenoceptor agonists used. By contrast, propranolol and the b 1 -adrenergic antagonist atenolol produced a similar blocking effect on melatonin production in humans [Walker et al, 1996;Nathan et al, 1997]. These data, and those obtained in a recent study measuring the influence of specific b-blockade on melatonin production in humans, have revealed that b-blockers decrease melatonin release via specific inhibition of adrenergic b 1 -receptors [Stoschitzky et al, 1999].…”
Section: Discussionsupporting
confidence: 73%
“…In hypothalamic -pituitary dysfunction, the relationships between melatonin and GH are more apparent. Melatonin production increased in hypogonadotrophic hypogonadism, and treatment with atenolol was associated with suppression of nocturnal melatonin secretion but a brisk rebound in the morning and a considerably delayed peak excretion time [Walker et al, 1996]. Administration of propranolol decreased melatonin [Mayeda et al, 1998] and restored the gonadotropin response to gonadotropin-releasing hormone in anorexia [Pawlikowski and Zarzycki, 1999].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation